Implementation of Local Wisdom-Based Mangrove Forest Management Policy in Ruar Village, East Biak District - Iriawan, Hermanu; Basan, Sherina; Edyanto, Edyanto (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study aims to determine local wisdom-based mangrove forest management in Ruar Village, East Biak District. The research used is a descriptive qualitative approach, utilizing the theories of Van Meter and Van Horn. Data collection methods used were interviews, observation, and literature review. The data analysis techniques used were data collection, data reduction, data presentation, and conclusion drawing.Research shows that mangrove forest management in Kampung Ruar remains informal and based on local wisdom, requiring the development of formal standards and regulations. Key challenges include human, financial, and time resources, as well as institutional weaknesses and territorial rights. The implementing organization is unstructured and dependent on indigenous communities, necessitating capacity building. Implementers must be serious and conservation-oriented, with communication skills needing to be enhanced through collaborative coordination. Social, economic, and political conditions significantly influence management success.